Results 1 to 5 of 5

- Sep 4th 2009, 04:46 PM #1

- Joined
- Sep 2009
- Posts
- 2

- Sep 4th 2009, 06:17 PM #2

- Joined
- Aug 2007
- From
- USA
- Posts
- 3,111
- Thanks
- 2

- Sep 4th 2009, 09:42 PM #3

- Joined
- Sep 2009
- Posts
- 2

- Sep 4th 2009, 09:47 PM #4
,

Solving for z, you may multiply both sides with (z + 5)(z + 1), we get

(z + 4)(z + 1) = (z + 4)(z + 5) + (z + 5)(z + 1),

z^2 + 5z + 4 = z^2 +9z + 20 + z^2 + 6z + 5, rearranging

0 = (z^2 + z^2 - z^2) + (9z + 6z - 5z) + (20 + 5 - 4)

0 = z^2 + 10z + 21, factoring

0 = (z + 7)(z + 3),

thus, z = -3 and -7

I have plotted it below, see . . . .

- Sep 4th 2009, 09:49 PM #5